The question of good and narrative identity in Charles Taylor - Beatriz Zergers Prado (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
Modern life poses unprecedented challenges in dealing with the task of defining a stable identity and achieving self-fulfillment. It is possible sustain that is a legacy of Modernity that the personis the main character of her own life and configure it by means of autonomous decisions. It is true thatshe must decide, although she has to do so from deep convictions if she does not want to be influencedby a culture that —in Charles Taylor’s perspective— has trivialized the ideal of authenticity and hasexalted a freedom that increases individualism. This essay is focused on the actions full of significance and the adherence to true goods that shape the identity and its narrative. The basics are in the anthropology and ethics of the philosopher just mentioned.